Effect of fungicides on epiphytic yeasts associated with strawberry. Issue 3 (4th April 2013) - Debode, Jane; Van, Wendy; Creemers, Piet; Maes, Martine
Abstract We studied the effect of two commonly used fungicides on the epiphytic yeast community of strawberry. Greenhouse and field experiments were conducted applying Switch (cyprodinil plus fludioxonil) or Signum (boscalid plus pyraclostrobin) to strawberry plants. Yeasts on leaves and fruits were assessed on treated and untreated plants at several time points via plating and denaturing gradient gel electrophoresis (DGGE) analysis. The yeast counts on plates of the treated plants were similar to the control plants. Unripe fruits had 10 times larger yeast concentrations than ripe fruits or leaves. Some dominant yeast types were isolated and in vitro tests showed that they were at least 10 times less sensitive to Switch and Signum as compared with two important fungal strawberry pathogens Botrytis cinerea and Colletotrichum acutatum, which are the targets for the fungicide control. DGGE analysis showed that the applied fungicides had no effect on the composition of the yeast communities, while the growing system, strawberry tissue, and sampling time did affect the yeast communities. The yeast species most commonly identified were Cryptococcus, Rhodotorula, and Sporobolomyces. These results point toward the potential applicability of natural occurring yeast antagonists into an integrated disease control strategy for strawberry diseases.